Comparison of different magnet arrangement on performance of flux reversal permanent magnet (FRPM) machine - M. H. Remlan; R. Aziz; S Salimin (Institute of Advanced Engineering and Science, 2019)
This paper offers the analysis of performance of Flux Reversal Permanent Magnet (FRPM) machines with different type of magnet arrangements. There are two designs that have been proposed in this report, which one of them has a pair of permanent magnets (PM) with alternate polarities place on surface of stator tooth and the polarities of two adjacent PM at these two stators are identical. This PM arrangement is called as NS-SN configuration. Second design is NS-NS configuration that has different PM polarities on different stator tooth. By comparing this PM arrangement, generally the NS-NS configuration offers high speed and power. However, the NS-SN configuration shows higher maximum torque compared to the previous design. The design process for both configurations is completely using finite element analysis (FEA) which is JMAG-Designer. To make sure the coil phase is in correct position, the design configuration with coil arrangement tests are evaluated. Finally, each flux of both designs been observed by analyse their torque with various armature current density.